Moist heat cooking methods. - 4 0 16; Culinary Institute of America; 5 Culinary Institute of America (New York, 2007)
Moist-heat techniques{u2014}steaming, cooking foods en papillote, shallow poaching, deep poaching, and simmering-rely on liquid and/or water vapor as the cooking medium. Braising and Stewing are often thought of as peasant dishes because they frequently call for less tender (and less expensive) main ingredients than do other techniques. Monitoring cooking temperatures and times vigilantly and determining doneness accurately are key to a mastery of moist-heat methods.
DVD format.
Keywords: 2 -- 0; 6; Cooking.;Steaming (Cooking).;Braising (Cooking). -- 20; 20; 2